2005
DOI: 10.1377/hlthaff.24.4.1095
|View full text |Cite
|
Sign up to set email alerts
|

Does Medicaid Managed Care Affect Access To Care For The Uninsured?

Abstract: This study investigates whether the implementation of Medicaid managed care from 1994 to 2001 was associated with changes in access to care for the uninsured. We used regression analysis to examine relationships between changes in county-level Medicaid managed care activity over time and changes in four measures of perceived access to care. After we controlled for sex, race, ethnicity, poverty, age, health, and education and included county fixed effects to account for unobserved county characteristics that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Regarding our interest in questions about individuallevel impacts, some MMC programs led to improved or unchanged access for Medicaid recipients, while other programs manifested enduring access barriers (Baker and Afendulis 2005;Berman, Armon, and Todd 2005;Fairbrother et al 2005;Sommers 2005;Seligman et al 2007); MMC exerted no consistent effects on access for the uninsured (Haberer, Garrett, and Baker 2005). Utilization under MMC proved inconsistent, even involving services targeted for reduction such as emergency department visits (Alessandrini et al 2001b;Garrett, Davidoff, and Yemane 2003;Davidoff et al 2007).…”
Section: Background On MMCmentioning
confidence: 99%
“…Regarding our interest in questions about individuallevel impacts, some MMC programs led to improved or unchanged access for Medicaid recipients, while other programs manifested enduring access barriers (Baker and Afendulis 2005;Berman, Armon, and Todd 2005;Fairbrother et al 2005;Sommers 2005;Seligman et al 2007); MMC exerted no consistent effects on access for the uninsured (Haberer, Garrett, and Baker 2005). Utilization under MMC proved inconsistent, even involving services targeted for reduction such as emergency department visits (Alessandrini et al 2001b;Garrett, Davidoff, and Yemane 2003;Davidoff et al 2007).…”
Section: Background On MMCmentioning
confidence: 99%
“…(Cunningham 1999;Waitzkin et al, 2002) In a notable exception, however, it was reported in one study that, "safety-net providers are coping". (Haberer et al, 2005) Since the mid-2000s, there has been a relative lull in the literature concerning the effects of Medicaid managed care on safety-net hospitals, with a complete absence in the field of economics. This study revisits the issue for two reasons.…”
Section: Medicaid Managed Care and The Safety-netmentioning
confidence: 99%
“…Researchers also could benefit from better data on Medicaid managed care penetration (at the local level) as well as from information on capitation rates. There are some papers on the impact of Medicaid managed care (e.g., Aizer, Currie, and Moretti 2007;Haberer, Garrett, and Baker 2005;Long and Yemane 2005;Currie and Fahr 2004;Garrett, Davidoff, and Yemane 2003), but more questions could be answered with additional data. % Policy parameters.…”
Section: Current Database Effortsmentioning
confidence: 99%